2005
DOI: 10.1039/b414832k
|View full text |Cite
|
Sign up to set email alerts
|

Measuring reaction kinetics in a lab-on-a-chip by microcoil NMR

Abstract: A microfluidic chip with an integrated planar microcoil was developed for Nuclear Magnetic Resonance (NMR) spectroscopy on samples with volumes of less than a microliter. Real-time monitoring of imine formation from benzaldehyde and aniline in the microreactor chip by NMR was demonstrated. The reaction times in the chip can be set from 30 min down to ca. 2 s, the latter being the mixing time in the microfluidic chip. Design rules will be described to optimize the microreactor and detection coil in order to dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
142
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(144 citation statements)
references
References 20 publications
1
142
0
1
Order By: Relevance
“…The microfluidic NMR chips were designed using CleWin Layout Editor version 4.3.3.0 (WieWeb Software, Hengelo, the Netherlands) and fabricated by Micronit Microfluidics BV, Enschede, the Netherlands, using standard microfabrication techniques similar to the ones previously described 40 . The chips have a standard format of 1.5 Â 4.5 cm, with rounded V-shaped channels wet-etched 500 mm deep in the bottom of a 1.1 mm thick borosilicate glass wafer.…”
Section: Methodsmentioning
confidence: 99%
“…The microfluidic NMR chips were designed using CleWin Layout Editor version 4.3.3.0 (WieWeb Software, Hengelo, the Netherlands) and fabricated by Micronit Microfluidics BV, Enschede, the Netherlands, using standard microfabrication techniques similar to the ones previously described 40 . The chips have a standard format of 1.5 Â 4.5 cm, with rounded V-shaped channels wet-etched 500 mm deep in the bottom of a 1.1 mm thick borosilicate glass wafer.…”
Section: Methodsmentioning
confidence: 99%
“…Trumbull et al 16 integrated a planar microcoil on a capillary electrophoresis (CE) chip, demonstarting a linewidth of less than 1.5 Hz of a 30 nL sample of water. Wensink et al 15 measured reaction kinetics of imine formation from benzaldehyde and aniline. Popovic et al 17 recorded spectra of mammalian cells with a sample volume corresponding to as little as 1800 cells.…”
Section: Direct Detectionmentioning
confidence: 99%
“…10 A microreactor chip that uses NMR detection has also been reported recently. 11 Ultrafast 2D methods have been applied to reaction transformations. 12 Finally, Hoye et al have shown that these NMR studies can easily be conducted in protonated solvents, 13 and dubbed this 'No-D' NMR.…”
Section: Introductionmentioning
confidence: 99%